2020
DOI: 10.3390/met10010076
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Central Segregation of Continuously Cast Billet on Banded Microstructure and Mechanical Properties of Section Steel

Abstract: The solidification structure and segregation of continuously cast billets produced by different continuous casting processes are investigated to elucidate their effect on segregated bands in hot-rolled section steel. It suggested that segregated spots are mainly observed in the equiaxed crystal zone of a billet. The solidification structure is directly related to superheating and the intensities of secondary cooling. To a certain extent, the ratio of the columnar crystal increases with the increase of superhea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Regarding the processing techniques and the evaluation of mechanical properties, different research lines were followed. Guo et al [5] evaluated the casting process conditions on the mechanical properties of hot-rolled steel and studied the billet quality by developing and optimisation method. Khosravani et al [6] tackled the microstructural changes that occur during the processing of dual-phase steels by using multiresolution spherical indentation stress-strain tests.…”
Section: Contributionsmentioning
confidence: 99%
“…Regarding the processing techniques and the evaluation of mechanical properties, different research lines were followed. Guo et al [5] evaluated the casting process conditions on the mechanical properties of hot-rolled steel and studied the billet quality by developing and optimisation method. Khosravani et al [6] tackled the microstructural changes that occur during the processing of dual-phase steels by using multiresolution spherical indentation stress-strain tests.…”
Section: Contributionsmentioning
confidence: 99%
“…For example, the failure of the axle pipe used for vehicle transportation will cause serious traffic accidents and endanger the safety of life and property. Most of the reasons for the failure of the pipe come from the internal quality of the product, such as the banded structure and uneven distribution of elements [3][4][5][6]. These defects were mainly inherited from the spot segregation inside the continuous casting billet, so optimizing the internal quality of the billet is one of the effective ways to fundamentally solve the internal defects of the pipe [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The failure of oil pipe is mainly related to the internal banded structure, and the spot segregation defect in the central equiaxed crystal zone of the billet is one of the main reasons for the banded structure [8][9][10]. Some studies have shown that with the decrease of the intensity of electromagnetic stirring in the mould or secondary cooling zone, the proportion of the central equiaxed crystal zone decreases, thereby reducing the number of spot segregation in the billet, and finally controlling the banded structure defect in the finished product [11][12][13].…”
Section: Introductionmentioning
confidence: 99%